Penile Enhancement Procedures with Simultaneous Penile Prosthesis Placement. (28th June 2012) - Hakky, Tariq S.; Suber, Jessica; Henry, Gerard; Smith, David; Bradley, Paul; Martinez, Daniel; Carrion, Rafael E.
Abstract : Here we present an overview of various techniques performed concomitantly during penile prosthesis surgery to enhance penile length and girth. We report on the technique of ventral phalloplasty and its outcomes along with augmentation corporoplasty, suprapubic lipectomy, suspensory ligament release, and girth enhancement procedures. For the serious implanter, outcomes can be improved by combining the use of techniques for each scar incision. These adjuvant procedures are a key addition in the armamentarium for the serious implant surgeon.